Salivary biomarkers: Relationship between oxidative stress and alveolar bone loss in chronic periodontitis. (January 2014) - Miricescu, Daniela; Totan, Alexandra; Calenic, Bogdan; Mocanu, Brandusa; Didilescu, Andreea; Mohora, Maria; Spinu, Tudor; Greabu, Maria
Abstract Objectives. Oxidative stress is implicated in the pathogenesis of many systemic and oral diseases such as periodontal disease. The main aim of this study is to explore a possible association between salivary markers of OS and alveolar bone loss. Materials and methods. The study included 20 patients with chronic periodontitis and 20 controls. Salivary OS biomarkers 8-hidroxy-desoxguanosine (8-HOdG), malondialdehyde (MDA), uric acid, total antioxidant capacity (TAC) and glutathione peroxidase (GPx) were evaluated. Bone loss markers such as C-terminal telopeptide of type I collagen (CTX I), matrix metalloproteinases-8 (MMP-8), osteocalcin and 25-hydroxy vitamin D3 (25- OH D) were detected in this study. The methods included general biochemical tests and ELISA. Results. Salivary 8-OHdG, MDA levels were significantly higher in the chronic periodontitis group compared with controls (p < 0.05). Salivary activities for uric acid, TAC and GPx were significantly decreased in patients with chronic periodontitis vs controls (p < 0.05). Salivary levels for CTX I, MMP-8, 25-OH D and Osteocalcin were significantly higher in the chronic periodontitis group compared to the controls (p < 0.05). A significant positive correlation was observed between salivary levels of MDA and CTX I. Significant negative correlations between uric acid and CTX I and between MMP-8 and uric acid have been found. Significant positive correlations were observed between CTX I, MMP-8, 25-OH D, osteocalcin and clinical parameters of periodontal disease. Conclusions. Important oxidative stress associated with alveolar bone loss biomarkers can be detected in saliva of patients with periodontal disease.